2004
DOI: 10.1007/s00441-004-0880-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of expression of cyclin D1/CDK4 complex in human placenta during gestation

Abstract: Progression through the cell cycle in eukaryotic cells is controlled by a family of protein kinases, termed cyclin-dependent kinases (CDKs), and their specific partners, the cyclins. In particular, the control of mammalian cell proliferation occurs largely during the G1 phase of the cell cycle. Five mammalian G1 cyclins have been enumerated to date: cyclins D1, D2, and D3 (D-type cyclins), and cyclins E and E2. By the use of immunohistochemistry and immunoelectron microscopy, we observed that in the first trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…The presence of cyclins D1 and D3 in the nuclei of mesenchymal cells and labyrinthine trophoblast cells during late pregnancy might suggest their involvement in the maintenance of a welldifferentiated state. Similar to the situation in the human placenta (De Falco et al 2004), cyclins D1 and D3 were observed primarily in the endothelial cells. Since proliferation of endothelial cells is a prerequisite for the formation of new vessels and elongation of existing ones, cyclins D1 and D3 appear to be involved in the control of placental angiogenesis during the third trimester of gestation.…”
Section: Pcna and G1 Cyclinssupporting
confidence: 52%
“…The presence of cyclins D1 and D3 in the nuclei of mesenchymal cells and labyrinthine trophoblast cells during late pregnancy might suggest their involvement in the maintenance of a welldifferentiated state. Similar to the situation in the human placenta (De Falco et al 2004), cyclins D1 and D3 were observed primarily in the endothelial cells. Since proliferation of endothelial cells is a prerequisite for the formation of new vessels and elongation of existing ones, cyclins D1 and D3 appear to be involved in the control of placental angiogenesis during the third trimester of gestation.…”
Section: Pcna and G1 Cyclinssupporting
confidence: 52%
“…Double immunohistochemical labelling with cytokeratin 7 allowed clear identification of the EVT and their expression of the cell cycle regulators, thus ruling out any confusion with the large leucocyte population present in the decidua at early stages in gestation. Other studies on cell cycle regulators have either not reported on the EVT or not distinguished between proximal and distal cells of the cell columns (Deloia et al 1997;Bamberger et al 1999;Olvera et al 2001;De Falco et al 2004). The set of cell cycle regulators present in the cell column strongly suggests that the cells in both the proximal and distal parts do not acutely proliferate.…”
Section: Cip/kip Cell Cycle Inhibitorsmentioning
confidence: 92%
“…22,23 Human and animal placental expression studies suggest that cell cycle genes may differ in expression or function in women with hypertension in pregnancy or small for gestational age (SGA). 24,25 …”
Section: Introductionmentioning
confidence: 99%